2013
DOI: 10.1007/s13224-013-0467-2
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Amniotic Fluid Index with Perinatal Outcome

Abstract: Objective(s) We aimed to evaluate the predictive value of amniotic fluid index (AFI) (\5) for adverse perinatal outcome in terms of cesarean section for fetal distress, birth weight, meconium staining, Apgar scores, and cord pH at birth. Result(s) The cesarean section rate for fetal distress and low birth weight babies, \2.5 kg, was higher in patients with oligohydramnios (p = 0.048, 0.001, respectively). There was no significant difference in meconium staining, Apgar score at 5 min \7, and cord pH at birth be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
40
3
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(62 citation statements)
references
References 10 publications
15
40
3
4
Order By: Relevance
“…Bhagat, Indu in his study found NICU admission was present in 92% of AFI ≤5 group as compared to 71.4% in other group while 36% of AFI ≤5cm needed stay of more than 2 days versus 24% in other group. 20 In present study there was 10.7% of perinatal mortality overall. 21.03% among of AFI ≤5 group had perinatal mortality while as 0% in other group.…”
Section: Discussionsupporting
confidence: 45%
“…Bhagat, Indu in his study found NICU admission was present in 92% of AFI ≤5 group as compared to 71.4% in other group while 36% of AFI ≤5cm needed stay of more than 2 days versus 24% in other group. 20 In present study there was 10.7% of perinatal mortality overall. 21.03% among of AFI ≤5 group had perinatal mortality while as 0% in other group.…”
Section: Discussionsupporting
confidence: 45%
“…14 In the study by Bhagat M et al, 12.5% had AFI <5.00 cm, while 87.5% had AFI >5.00 cm, similarly in the study by Alchalabi HA et al, 37% patients had AFI <5.00 cm while 63% had AFI >5.00 cm. 15,16 Our findings regarding NST has been found to be similar to the study by Lohana RU et al, where 85% had reactive and 15% had non-reactive NST at admission. 17 In the study by Shreshtha P et al Cat.-I is 77%, Cat.-II 9%) and Cat.-III 20% while in the study by Rahman H et al; Cat.-I is 77.0%, Cat.-II 14%) and Cat.-III 9%.…”
Section: Discussionsupporting
confidence: 91%
“…The occurrence of low birth weight was 35% which is comparable with that of other studies as Bhagat et al, Biradar KD et al in which the percentage of low birth rate was 56% and 38.6% respectively. 7,10 Apgar score <7 at 5 minutes of birth was found in 7% patients in those with oligohydramnios and 4% in normal AFI group which is not statistically significant. The results are comparable with that of other studies such as in Umber et al, Padmini CP et al, Bhagat Chawla et al the percentage of babies with Apgar score <7 at 5 minutes of birth was 6%, 8% and 4% respectively.…”
Section: Discussionmentioning
confidence: 69%
“…The results are comparable with that of other studies such as in Umber et al, Padmini CP et al, Bhagat Chawla et al the percentage of babies with Apgar score <7 at 5 minutes of birth was 6%, 8% and 4% respectively. 8,13,7 Admissions to neonatal intensive care unit were similar in both oligohydramnios and those with normal AFI. NICU admissions were 15% in oligohydramnios group due to various morbidities like birth asphyxia and meconium aspiration.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation